KEPATUHAN ORANG TUA TENTANG DIET GLUTEN FREE DAN CASEIN FREE DENGAN PERILAKU ANAK AUTIS - Rahmah, Jannatur; Diani, Noor; Rachmawati, Kurnia (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2015)
Avoiding food containing gluten and casein is one of the efforts to reduce autistic behaviorsbecause the two substances can effect the central nerve system which leads to behavioralabnormality. The parents’ compliance with the diet should be consistent to improve the behaviors ofautistic children. The purpose of the study was to find out the relationship between the parents’compliance with gluten free and casein free diet and the behaviors of austistic children. This study wasan observational analytical research which employed cross sectional approach with a totalrespondents of 31 people and utilized purposive sampling method. This study was used Sprearman’sCorrelation test. The result of the study indicated that the correlation coefficient was 0,453 and thesignificance of research results was 0,010 it could be inferred that the relationship between theparents’ compliance with gluten free and casein free diet and the behaviors of autistic children hadmedium, significant and negative correlation (irrelevant). It was suggested that the parents’ shouldlook for the information about gluten free and casein free diet through mass media, seminars,talkshows, or trainings and apply gluten free and casein free diet to autistic children.